Non‐unit protection method for long transmission lines in MTDC grids - Seyed Sattar Mirhosseini; Sadegh Jamali; Marjan Popov (IET Generation, Transmission & Distribution, 2021)
Abstract This paper presents a non‐unit protection method for long transmission lines of multi‐terminal HVDC (MTDC) grids based on the magnitude and direction of modal voltage and current travelling waves. The method overcomes the difficulty resulting from high attenuation and distortion as reported in previous methods using fault‐generated transients for protection of long HVDC lines. The proposed method determines the faulted pole using multi‐resolution morphological gradient of the pole voltage. Then, the multiplication of multi‐resolution morphological gradient of the modal travelling waves is utilised as a criterion to discriminate between internal and external faults and non‐fault events. The criterion is a negative high value for internal faults, a negative low value for forward external faults and events, and a positive value for backward external faults and events. A four‐terminal HVDC grid with modular multilevel converters including long HVDC lines is modelled using the PSCAD/EMTDC software. The simulation study validates effectiveness of the method for detection and discrimination of high resistance faults on long lines, as well as stability against external DC and AC faults, and DC circuit breaker opening and reclosing transients. The proposed method uses a relatively low sampling frequency and local data, i.e. no requirement for a communication link.